The Valuation of Netiquette of Primary Teachers in Digital Era - Meylina, Meylina; Jufri, Allen Christy (Faculty of Education Universitas Negeri Malang, 2024)
Internet etiquette is very necessary as teachers increasingly use the internet in teaching and communicate online. Netiquette is introduced in schools so that teachers would be more ethical in utilizing and dealing with the dynamics of interactions in the digital space wisely. The purposes of this study were to know the level of teachers’ understanding on netiquette in digital use and to describe factors that influence it. This study used phenomenological research method. The data were collected through observation sheets which distributed to 15 teachers from several schools on google form. The results indicated that the majority of teachers already understand that in cyberspace, humans interact and communicate with various cultural differences. Easy internet access allows everyone to connect and participate, without cultural or geographic boundaries. So, netiquette needs to be implemented by all internet users, both in the field of education and social media. Cyber-bullying is a case that needs to be recognized and anticipated as early as possible. For this reason, apart from teachers, it is also important to socialize netiquette to all students at elementary to high school levels.